If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6x = 52 Combine like terms: 5x + 6x = 11x 11x = 52 Solving 11x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '11'. x = 4.727272727 Simplifying x = 4.727272727
| 16*11-9*11= | | -4(x^2-18.75x)=0 | | 1875-588m^90=0 | | 8+2p-6=9p+8-4p | | -7/3v+4/5=-1/5v-7 | | 61-2x=6x+18 | | 141-6=3x+15 | | 24x/260/(1.05) | | x(75-4x)=0 | | 11(t-5)+4t=5(3t+3)-10 | | 2/3a=-4 | | in(7-3x)=1.75 | | 75.00+25.00=40.00x | | 18=b+5*5*5 | | 1-7x=7x+43 | | -22=4y-8-6y | | -4(-4)+6y=-24 | | 0=x+2 | | 139-6x=30x+15 | | mx=x-5n | | 2p+2p=8 | | 1/4(p-5)=3 | | 3/10x+15-8/12x+18 | | (z/18)=-25 | | u^4-6u^2+9-z^2-4zy-4y^2=0 | | -(5y+1)-(-4y-2)=0 | | 62=2b | | I=mv-mu | | 3(2n-7)-3=36 | | y=-(-2)+1 | | 5(x+-2)=2x+(x+6) | | 2x+30=8x+2 |